Методические принципы физической реабилитации больных с грыжами передней брюшной стенки - Пархотик, Иван; Parkhotik, Ivan (Східноєвропейський національний університет ім. Лесі Українки, 2012)
В статье проанализированы методические принципы физической реабилитации больных с грыжами передней брюшной стенки, зависящие от клинико-функционального состояния пациентов. Программа физической реабилитации включает физические упражнения, массаж и физиотерапию, направленные на обеспечение необходимых условий для проведения хирургического лечения грыж: укрепление мышц брюшного пресса, подготовку больных к операции, предупреждение развития ранних и отдалённых послеоперационных осложнений. Физическая реабилитация носит опережающий характер лечебного воздействия на организм. Указаны особенности применения физических упражнений в зависимости от размера и локализации грыжи. Methodological principles of physical rehabilitation of the ill with abdominal hernia that depend on clinical and functional condition of patients are analyzed in the article. Program of physical rehabilitation includes physical exercises, massage and physiotherapy, aimed at securing of necessary conditions for conducting of surgical treatment of hernias: strengthening of muscles of peritoneal cavity, preparation of the ill to operation, prevention of the development of early and remote after-operational complications. Physical rehabilitation has prior character of medical influence on organism. There is also given information on peculiarities of applying of physical exercises depending on size and localization of hernia.
Methodological Principles of Physical Rehabilitation of the ill with Abdominal Hernia
Keywords: грыжи передней брюшной стенки; физическая реабилитация; лечебная гимнастика; массаж; физиотерапия; abdominal hernia; physical rehabilitation; therapeutic exercises; massage; physiotherapy